Erratum to the paper Bogdan, M., ”Some comments on a linear programming problem” - BOGDAN, Marcel (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
The present paper corrects an assertion of the author from [1]. The pivoting algorithms referred to, search for solving the linear programming problem. Mathematics Subject Classification (2010): 90C05. Received 6 February 2020; Accepted 31 March 2020.